2011
DOI: 10.4061/2011/970983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of P4 Nuclease from Leishmania infantum

Abstract: Parasite of the genus Leishmania is reliant on the salvage pathway for recycling of ribonucleotides. A class I nuclease enzyme also known as P4 nuclease is involved in salvage of purines in cutaneous Leishmania species but the relevant enzymes have not been characterized in Leishmania infantum (L. infantum). The aim of this study was to clone and characterize the gene encoding class I nuclease in L. infantum. DNA extracted from L. infantum was used for amplification of P4 nuclease gene (Li-P4) by PCR. The prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…Western blot analyses have shown that the P4 nuclease of L. infantum is expressed in both promastigotes and amastigotes. However, in accordance with previous studies involving this enzyme, its expression is significantly higher in amastigote parasites (Farajnia et al, 2011).…”
Section: Amastigote Stage-specific Class I Nucleases P4/lmc1nsupporting
confidence: 92%
See 2 more Smart Citations
“…Western blot analyses have shown that the P4 nuclease of L. infantum is expressed in both promastigotes and amastigotes. However, in accordance with previous studies involving this enzyme, its expression is significantly higher in amastigote parasites (Farajnia et al, 2011).…”
Section: Amastigote Stage-specific Class I Nucleases P4/lmc1nsupporting
confidence: 92%
“…Comparative sequence analyses have shown high homology to the P4 nucleases of L. donovani, L. major and L. pifanoi. The alignment results confirmed the existence of the five conserved domains of class I nucleases (Farajnia et al, 2011). Western blot analyses have shown that the P4 nuclease of L. infantum is expressed in both promastigotes and amastigotes.…”
Section: Amastigote Stage-specific Class I Nucleases P4/lmc1nsupporting
confidence: 71%
See 1 more Smart Citation
“…So far, different studies have been conducted to clone, express or manipulated Leishmania genes. Cloning and characterization of a gene encoding class I nuclease in L. infantum has already been carried out by Farajnia et al [20]. Also, there are other reports on cloning and expression of different Leishmania genes such as HSP70 and glucose-regulated protein 94 (GRP94) gene from L. infantum [21,22], surface protein encoding genes from L. major [23,24] and L. donovani avastin gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…At present, chemotherapy is the most common therapeutic strategy against leishmania. However, emergence of drug-resistant parasites has limited conventional therapeutic approaches (Farajnia et al 2011) (Rahbarnia et al 2012). In this respect, researchers have examined the application of RNAi technology to harness leishmaniasis disease.…”
Section: Rna Interference-based Therapeutics To Combat Infectionsmentioning
confidence: 99%